Assessment of the Accuracy of High-Throughput Sequencing of the ITS1 Region of Neocallimastigomycota for Community Composition Analysis - Edwards, Joan E.; Hermes, Gerben D. A.; Kittelmann, Sandra; Nijsse, Bart; Smidt, Hauke (Frontiers in Microbiology, 2019)
Anaerobic fungi (Neocallimastigomycota) are common inhabitants of the digestive tract of large mammalian herbivores, where they make an important contribution to plant biomass degradation. The internal transcribed spacer 1 (ITS1) region is currently the molecular marker of choice for anaerobic fungal community analysis, despite its known size polymorphism and heterogeneity. The aim of this study was to assess the accuracy of high-throughput sequencing of the ITS1 region of anaerobic fungi for community composition analysis. To this end, full-length ITS1 clone libraries from five pure cultures, representing the ITS1 region size range, were Sanger sequenced to generate a reference dataset. Barcoded amplicons of the same five pure cultures, and four different derived mock communities, were then sequenced using Illumina HiSeq. The resulting sequences were then assessed in relation to either the reference dataset (for the pure cultures) or the corresponding theoretical mock communities. Annotation of sequences obtained from individual pure cultures was not always consistent at the clade or genus level, irrespective of whether data from clone libraries or high-throughput sequencing were analyzed. The detection limit of the high-throughput sequencing method appeared to be influenced by factors other than the parameters used during data processing, as some taxa with theoretical values >0.6% were not detected in the mock communities. The high number of PCR cycles used was considered a potential explanation for this observation. Accuracy of two of the four mock communities was limited, and this was speculated to be due to preferential amplification of smaller sized ITS1 regions. If this is true, then this is predicted to be an issue with only six of the 32 named anaerobic fungal clades. Whilst high-throughput sequencing of the ITS1 region from anaerobic fungi can be used for environmental sample analysis, we conclude that the accuracy of the method is influenced by sample community composition. Furthermore, ambiguity in the annotation of sequences within pure cultures due to ITS1 heterogeneity reinforces the limitations of the ITS1 region for the taxonomic assignment of anaerobic fungi. In order to overcome these issues, there is a need to develop an alternative taxonomic marker for anaerobic fungi.